The problems of interpreter's mistake while simultaneous interpreting of political leader's speech - Ruzimbaev Umarjon Xajiboy o'g'li (Zien Journals, 2023)
This article delves into the challenges faced by interpreters while conducting simultaneous interpretation of political leader's speeches. It examines the potential consequences of mistakes and their implications on communication and diplomacy.
Keywords: Simultaneous interpreting; Political leader's speech; Interpreter mistakes